Response to the European Consultation on the Future of the Europe 2020 Strategy. - (:unkn) unknown (My University, 2014)
The German Academy for Spatial Research and Planning (ARL) welcomes the consultation process on the mid-term review and future perspectives of the Europe 2020 Strategy. The Europe 2020 Strategy, including experiences so far and ideas for its future, has induced intense and interesting discussions. Given the broad character of the Strategy, a wide range of different perspectives emerge in such discussions. As part of the consultation process the ARL contributes to the comprehensive discussion of the Europe 2020 Strategy with this position paper, focusing exclusively on certain key points. Within these key points, the ARL highlights the territorial and regional development dimension of the implementation of the Europe 2020 Strategy, contributing not only to growth but also to the Lisbon Treaty goal that aims to achieve more territorial cohesion in Europe. With regard to the further development of the Europe 2020 Strategy the objective is to present key aspects that the ARL view as worth pursuing. The positions presented below follow the main headings and the questions of the consultation process.
Keywords: Raumordnungspolitik; Raumplanung; Regionalentwicklung; Wirtschaftsentwicklung; Entwicklungsprogramm; Wirtschaftsplanungsprogramm; Entwicklungsstrategie; Europäische Union